Workplace Indicators of Mood: Behavioral and Cognitive Correlates of Mood Among Information Workers - Mark, Gloria; Czerwinski, Mary; Iqbal, Shamsi; Johns, Paul (ACM Digital Health, 2016)
Positive wellbeing in the workplace is tied to better health. However, lack of wellbeing in the workplace is a serious problem in the U.S, is rising continually, and can lead to poor health conditions. In this study we investigate factors that might be associated with workplace wellbeing. We report on an in situ study in the workplace of 40 information workers whose mood was tracked for 12 days. We used a mixed-methods study using Fitbit actigraphs to measure sleep and physical activity, computer logging, and repeated daily surveys. We found that sleep and perceived productivity are positively correlated with affect balance (the balance of positive and negative affect), whereas concentration difficulty, and amount of time on workplace email, are negatively correlated with affect balance. Our model explains 48% of the variance of workplace mood. We discuss the value and challenges of multi-faceted measures of health as we move towards designing interdisciplinary digital health research.